2019
DOI: 10.4236/jtr.2019.73016
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Health Education Video in Improving Treatment Adherence among Patients with Tuberculosis: An Interventional Study from Bengaluru, India

Abstract: Background: Non-adherence to tuberculosis (TB) treatment might prolong disease transmission and also increases the risk of drug resistance. Various studies have been carried out to determine the predictors of non-adherence but intervention-based studies to address treatment adherence are scarce. This study intends to estimate the treatment adherence rates following delivery of patient-centered health education videos in the intervention tuberculosis unit (TU) and to compare the treatment adherence with that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Scientific data have also discovered that patients have an optimistic attitude towards implementation of mHealth strategies [ 24 ]. After meticulous analysis it was explored that among the all the interventions, patients preferred video-based Direct Observation Treatment (DOT) followed by SMS and voice calls [ 26 , 30 , 32 ]. Contradicting this finding, a cross sectional study conducted in Pune put forth that the result acceptability of text messages was found to be minimal among TB patients [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scientific data have also discovered that patients have an optimistic attitude towards implementation of mHealth strategies [ 24 ]. After meticulous analysis it was explored that among the all the interventions, patients preferred video-based Direct Observation Treatment (DOT) followed by SMS and voice calls [ 26 , 30 , 32 ]. Contradicting this finding, a cross sectional study conducted in Pune put forth that the result acceptability of text messages was found to be minimal among TB patients [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study in Bengaluru, India reported an increase in medication adherence by TB patients after being given an educational video highlighting essential TB information and emphasizing the importance of completing treatment. 29 In another study, it was reported that educational video could increase disease prevention behavior. 30 Furthermore, the effectiveness of using leaflet as a health promotion medium has been extensively reported.…”
Section: Introductionmentioning
confidence: 99%